Prospectus 2008/2009 : Distance Education Centre : Gateway to Opportunity / Institute of Education Development, UiTM - Institute of Education Development Centre, UiTM (Institute of Education Development Centre (InED), UiTM, 2008)
This illustrative and comprehensive prospectus is our way of assisting prospective students to have a better understanding on the courses and programmes offered in MARA University of Technology a distance learning. It is hoped that this prospectus will definitely be electronic (e-PJJ) handy. It should answer all your initial questions about InED, and about the course you are about to follow. InED UiTM will continue to ensure that there are more opportunities for bumiputras to acquire new knowledge, improve their skills, and further their education. I sincerely hope that all bumiputras will avail themselves to these opportunities to enhance their knowledge and facilitate their professional advancement.